The Development of a Multidimensional Inventory for the Assessment of Mental Pain (FESSTE 30) - Flenreiss-Frankl, Karin; Fuchshuber, Jürgen; Unterrainer, Human Friedrich (Frontiers in Psychology, 2021)
Background: Although the term “mental pain” is often the subject of expert opinions regarding claims for damages, there is still no standardized questionnaire in the German-speaking area to operationalize this concept. Therefore, the aim of this work is the development and validation of a self-assessment measurement for psychological pain after traumatic events (FESSTE). Methods: A first version of the questionnaire was applied on a sample of the Austrian general population (N = 425). After performing an item analysis and exploratory factor analysis, the questionnaire was shortened and tested on a second general population sample (N = 619). This version was then evaluated and adapted using a confirmatory factor analysis. Finally, the newly developed questionnaire was related to the extent of traumatization (measured with a uniquely designed trauma checklist attached to the FESSTE) and already established instruments for the assessment of psychiatric symptom burden, which included the Brief Symptom Inventory-18 (BSI-18) and the Posttraumatic-Stress-Scale (PTSS-10). Results: The final version of the FESSTE consists of a total of 30 items and covers the subscales "Somatization", "Depression", "Intrusive Memories", "Dissociation" and "Anxiety", and a total scale "Mental Pain". Based on the confirmatory factor analysis, it is assumed that the latent factor structure of the FESSTE can be best described as a bifactor-model. The final version shows a satisfactory model fit, high internal consistencies and strong positive correlations with the BSI-18 and PTSS-10, as well as the extent of traumatic experiences. Discussion: The FESSTE enables an operationalization of mental pain comprising five subscales and one total scale. What is more, the trauma checklist attached to the FESSTE allows for the standardized assessment of potentially traumatic experiences and the corresponding extent of these experiences. The results indicate that the FESSTE is a reliable and valid self-assessment procedure for mental pain, which is suitable for use in research and in expert practice.